VALIDITAS E-MODUL IPS LECTORA INSPIRE BERBASIS DISCOVERY LEARNING UNTUK KELAS IV SEKOLAH DASAR - Yulfia Nora; Ira Rahmayuni Jusar; Ade Fitri Rahmadani; Tiwi Aulia Safitri (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
During the Covid-19 pandemic, the implementation of online learning carried out by teachers, tended to only use the WhatsApp application as a medium in assigning assignments and collecting assignments by students. Learning resources used by students at home are not yet innovative, only sourced from books and Student Worksheets (LKS). In addition, the social studies material contained in the book is not in accordance with the curriculum. This research aims to describe the validity of the IPS Lectora Inspire e-module based on discovery learning for the fourth grade of elementary school. The research method used is Research and Development (R&D). This research is a research method used to find, develop and validate a product. This research went through three stages, namely the define, design and develop stages which were adopted from the 4-D model developed by Thiagarajan which was then modified into 3-D. The data collection technique uses a questionnaire. The instrument for collecting research data is in the form of a validity questionnaire sheet. The e-module is validated by two experts, namely a material expert and a design expert. The data from the validation sheet were analyzed quantitatively, then used descriptive techniques to draw conclusions qualitatively. Based on the results of data analysis, the validity of the material aspect was 89% and the validity of the design aspect was 83% with an average of 86% with very valid criteria. Thus, the IPS Lectora Inspire e-module based on discovery learning for grade elementary school produced can be used in the learning process.